The study of sequences defined by a first order recursion by means of a pocket calculator - Tuzson, Zoltán (Teaching Mathematics and Computer Science, 2013)
This paper will present the way we can use a simple pocket calculator to teach mathematics. Namely, a pocket calculator can be very useful to study the properties of sequences defined by first order recursion (e.g. monotonicity, boundedness and convergence) and to gain a deeper understanding.